An update on angiotensin-converting enzyme 2 structure/functions, polymorphism, and duplicitous nature in the pathophysiology of coronavirus disease 2019: Implications for vascular and coagulation disease associated with severe acute respiratory syndrome coronavirus infection - Devaux, Christian A.; Camoin-Jau, Laurence (Frontiers in Microbiology, 2022)
It has been known for many years that the angiotensin-converting enzyme 2 (ACE2) is a cell surface enzyme involved in the regulation of blood pressure by counteracting ACE. More recently, it was proven that to enter susceptible human cells, the severe acute respiratory syndrome coronavirus (SARS-CoV-2) interacts with ACE2. This functional duality of ACE2 tends to explain why this molecule plays such an important role in the clinical manifestations of coronavirus disease 2019 (COVID-19). At the very start of the pandemic, a publication from our Institute (entitled "ACE2 receptor polymorphism: susceptibility to SARS-CoV-2, hypertension, multi-organ failure, and COVID-19 disease outcome" by Devaux et al., 2020; more than 400 citations to date), was one of the first reviews linking COVID-19 to the duplicitous nature of ACE2. However, even given that COVID-19 pathophysiology may be driven by an imbalance in the renin-angiotensin system (RAS), we were still far from understanding the complexity of the mechanisms which are controlled, in part, by ACE2 expression in different cell types. To gain insight into the physiopathology of SARS-CoV-2 infection, it is of crucially important to consider the polymorphism of the ACE2 gene and the existence of alternative isoforms of ACE2. Over the past two years, an impressive amount of new results have come to shed light on the role of ACE2 in the pathophysiology of COVID-19, requiring us to update our analysis. Genetic linkage studies have been reported that highlight a relationship between ACE2 genetic variants and the risk of developing hypertension. Currently, many research efforts are being undertaken to try to understand the links between ACE2 polymorphism and the severity of COVID-19. In this review, we discuss the link between the SARS-CoV-2 spike glycoprotein interaction with ACE2 and the development of a cytokine storm associated microvascular injury and obstructive thrombo-inflammatory syndrome, which represent the primary causes of severe forms of COVID-19 and lethality among SARS-CoV-2-infected patients. Finally, we summarize the therapeutic strategies aimed at preventing the severe forms of COVID-19 that target ACE2. Changing paradigms may help improve patients' therapy.